2016
DOI: 10.1016/j.jfda.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatography (HPLC) fingerprints and primary structure identification of corn peptides by HPLC-diode array detection and HPLC-electrospray ionization tandem mass spectrometry

Abstract: Corn peptides (CPs) are reported to have many biological functions, such as facilitating alcohol metabolism, antioxidation, antitumor, antihypertension, and hepatoprotection. To develop a method for quality control, the high-performance liquid chromatography (HPLC) system was applied. Twenty-eight common peaks were found in all the CPs of corn samples from Enshi, China, based on which, a fingerprinting chromatogram was established for use in quality control in future research. Subsequently, the major chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…The results of electrophoresis analysis such as sodium dodecyl‐sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) can reveal the MW distribution of corn protein or hydrolysates (Malumba et al., ). Furthermore, the mass spectrometry (MS) technologies have already become a common method to analyze the amino acid sequences of CPs (Wang et al., ; Wang, He, Zhang, Li, & Ma, ). The primary structure of CPs can be identified by RP‐HPLC‐MS/MS (Ma et al., ; Wang et al., ).…”
Section: Production Isolation Purification and Characterization Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of electrophoresis analysis such as sodium dodecyl‐sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) can reveal the MW distribution of corn protein or hydrolysates (Malumba et al., ). Furthermore, the mass spectrometry (MS) technologies have already become a common method to analyze the amino acid sequences of CPs (Wang et al., ; Wang, He, Zhang, Li, & Ma, ). The primary structure of CPs can be identified by RP‐HPLC‐MS/MS (Ma et al., ; Wang et al., ).…”
Section: Production Isolation Purification and Characterization Ofmentioning
confidence: 99%
“…Wang et al. () employed an RP‐HPLC‐MS/MS with a DAD detector to systematically identify the primary structures of CPs, and 48 peptide fractions were obtained.…”
Section: Production Isolation Purification and Characterization Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Wang et al reported 28 different polypeptide sequences that possessed many biological functions, such as antioxidant activity, antihypertensive effects, alcohol metabolism and antitumor effects. 4 Other studies have indicated that the absorptive rate of intact peptides from protein hydrolysates may even be faster than that of free amino acids and that the energy consumption required to assimilate peptides may be lower than that required to assimilate equivalent amino acids. 5 Therefore, the investigation of small peptides with biological activities is critical for studies of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic fingerprint analysis has been accepted as a strategy for quality assessment of herbal medicines and preparations by the WHO, the FDA, and China Food and Drug Administration (CFDA). It combines chromatographic techniques, such as CE , GC and HPLC , with sensitive and selective detectors like photodiode array detection (PDA) , evaporative light‐scatter detection (ELSD) and MS to construct specific patterns of recognition for multiple compounds in herbal drugs. The entire pattern of compounds can then be evaluated to determine not only the absence or presence of desired markers or actives but the complete set of ratios of all detectable analytes .…”
Section: Introductionmentioning
confidence: 99%